Heterodoxy and humour in the Nun's Priest's Tale, a study of the tale's clerical satire - Chamberlain, Hugh Jonathon (University of Waterloo, 1997)
The aim of this thesis, HETERODOXY AND HUMOUR IN THE NUN'S PRIEST'S TALE: A STUDY OF THE TALE'S CLERICAL SATIRE, is to demonstrate the following: first, that Chaucer's Nun's Priest's Tale ought to be considered in light of the ecclesiastical debates of the late fourteenth century; second, that Chaucer deliberately avoids having the tale suggest an either orthodox or heterodox affiliation; third, that the function of the tale is to satirize the ecclesiastical debates it invokes. With regard to the first of these aims, I will argue that six of the NPT's more substantial deviations from its source text, the Roman de Renart, allude to a variety of contentious issues that both orthodox and heterodox figures often addressed in their sermons and/or religious tracts. With regard to the second of these aims, I will examine the strategies employed in the NPT that allow the tale to maintain a neutral position in each of the issues it raises. For example, the NPT often speaks to points on which heterodox and orthodox writers concurred, thereby preventing its contemporary audience from detecting either a heterodox or orthodox sympathy and allowing the tale to speak without commitment. Finally, concerning the third of these aims, I will contend that Chaucer's purpose in invoking the ecclesiastical issues but offering no allegiance to either the heterodox or orthodox side is to satirize not one group in the debates, but rather the debates themselves. Moreover, the NPT generates a light-hearted parody of the debates, rather than a mean-spirited attack, by framing their discussion within the fantastic, non-threatening realm of the fable and by avoiding the appearance of partiality and/or dogmatism. The tale therefore succeeds in its declared purpose of entertaining its audience and it contributes to the Canterbury Tales' "peaceful conclusion" described by Charles Muscatine and to the Tales' "purpose in comedy" described by Laura Kendrick.
Keywords: Harvested from Collections Canada